Mining and analysis of chloroplast simple sequence repeats SSRs from eight species of Aquilaria - Hishamuddin, Muhammad Syahmi; Samsuddin, Ahmad Syazwan; Mohamed, Rozi (The Scientific and Technological Research Council of Tuerkiye, 2021)
Aquilaria is a tropical forest tree, producer of the famed and expensive agarwood. Aggressive collection of agarwood put strain on the natural stands of Aquilaria species, sparking efforts to domesticate the tree and cultivate agarwood in plantations. However, tree domestication progress is hampered by the scarcity of genomic resources that is crucial for breeding programs. In this study, the complete chloroplast (cp) genome sequences from eight Aquilaria species were analyzed in silico. For identification of the simple sequence repeats (SSRs), MISA PERL script which had a repeat length of 12 for mononucleotides (mono-), 6 for dinucleotides (di-), 4 for trinucleotides (tri-), 3 for tetranucleotides (tetra-), pentanucleotides (penta-), and hexanucleotides (hexa-), respectively, along with frequency were utilized. From a total of 312 SSRs that were discovered, merely 50 (16%) were found localized within the coding region while the majority (84%) were within the intergenic regions, with an average of one SSR per 4.5 kb. The mean length of the SSRs were 11.63 bp. Mono- repeats were the predominant motifs (29.2%), followed by tetra- (28.8%), di- (20.5%), tri- (19.9%), and penta- (1.6%). Whereas the most recurring motifs were A/T (97.8%) for mono-, AT/AT (87.5%) for di-, AAT/ATT (48.4%) for tri-, and AAAT/ATTT (45.6%) for tetra-. GO analysis using the REVIGO software identified four molecular functions, six biological processes and three cellular components. In conclusion, findings of this study offer a scientific foundation for future phylogenetics, evolutionary genetics, diversity studies and breeding programs on Aquilaria species.